Pengaruh Radiasi terhadap Struktur dan Fungsi Sel - Tiara Novianti Dadi Lado; Lidia Delvina Bhoki; Santiana E. Rithi; Tersius Soba; Veronika P. Sinta Mbia Wae (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Ionizing and non-ionizing radiation are widely used in health, industry, scientific research, and communication technology, but their use also has the potential to pose biological risks to humans. Therefore, a comprehensive understanding of the mechanisms of radiation interaction with biological tissues and their health implications is crucial. This study aims to systematically examine the biological effects of ionizing and non-ionizing radiation on human health, as well as the safety principles applied in their use. The research method used is a literature review by examining scientific articles, reports from international institutions, and relevant publications that discuss radiation exposure, biological impacts, and aspects of radiation protection. The results of the study indicate that ionizing radiation, such as X-rays and gamma rays, has the ability to ionize atoms and molecules, thus potentially causing DNA damage that can trigger deterministic and stochastic effects, including an increased risk of cancer. Although radiation doses in medical diagnostic procedures are generally below the hazardous threshold, the application of radiation protection principles in the form of justification, optimization, and dose limitation remains a key factor in ensuring the safety of patients and healthcare workers. While non-ionizing radiation from telecommunications devices does not cause ionization, at high exposure levels it can cause thermal effects on biological tissue, although most epidemiological studies have not shown a consistent link with an increased risk of cancer. Exposure to cosmic radiation during commercial flights and at high altitudes has the potential to cause dose accumulation, which requires special attention. The conclusion of this study emphasizes that radiation use must be accompanied by adequate scientific understanding, long-term risk evaluation, and the implementation of strict safety policies to ensure that the benefits of radiation use outweigh the risks.